Impact of sustainable mountain tourism on economic development: A systematic review - Dhungana, Bharat Ram (Journal of Tourism and Himalayan Adventures, 2025)
Sustainable mountain tourism focuses on economic, social, cultural, and environmental empowering tools that help to improve the well-being of the mountain community. This study examines the impact of sustainable mountain tourism on economic development using a systematic literature review. The research is based on a review of systematically selected empirical research papers. The Google Scholar search engine was applied using the keywords "tourism policy" and "sustainable mountain tourism". All papers that were published from January 2018 to February 2025 have been checked for the study and 29 research papers were selected for this study using the PRISMA framework. The study find effective governance mechanism and stakeholder engagement are essential factors of sustainable tourism development. The role of governments and stakeholders is crucial in developing and implementing sustainable mountain tourism. Sustainable mountain tourism practices ensure economic stability, empower the local economy and foster livelihood of mountain community. Government and policymakers may introduce economic, social and environmental initiatives to align sustainable mountain tourism practices with the economic interests of the local community.